1998
DOI: 10.1021/ma980758r
|View full text |Cite
|
Sign up to set email alerts
|

Polyphosphazenes Functionalized with Sulfone or Sulfoxide Groups:  Synthesis, Characterization, and Possible Polymer Electrolyte Applications

Abstract: A method for the introduction of sulfone or sulfoxide functional groups into the side groups of polyphosphazenes has been developed. This procedure involves the prior introduction of thioether-containing side groups into phosphazenes followed by oxidation of the sulfur atoms by H2O2 or m-chloroperbenzoic acid (MCPBA). This method was first explored at the level of model small molecule cyclic species as a prelude to the polymer oxidation reactions. The attractive forces generated by sulfone or sulfoxide functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 51 publications
1
30
0
Order By: Relevance
“…A certain degree of contradictory evidence can be found in literature on this regard: earlier reports claimed the oxidation of polysulfides to lead directly to sulfones, with sulfoxides present only as intermediates 163. On the other hand, using generally less‐drastic conditions (and, above all, reasonably low temperature154), sulfoxides have been unequivocally demonstrated to be the main oxidation product for main‐chain polymers, such as poly(ethylene sulfide),154 poly(hexamethylene sulfide)164 and polyphosphazenes,165 and for side‐chain polymers 166. Therefore, it can be assumed that, under “milder” conditions, polysulfoxides will be main product of the polysulfide oxidation.…”
Section: Preparative Strategies For Polysulfidesmentioning
confidence: 99%
“…A certain degree of contradictory evidence can be found in literature on this regard: earlier reports claimed the oxidation of polysulfides to lead directly to sulfones, with sulfoxides present only as intermediates 163. On the other hand, using generally less‐drastic conditions (and, above all, reasonably low temperature154), sulfoxides have been unequivocally demonstrated to be the main oxidation product for main‐chain polymers, such as poly(ethylene sulfide),154 poly(hexamethylene sulfide)164 and polyphosphazenes,165 and for side‐chain polymers 166. Therefore, it can be assumed that, under “milder” conditions, polysulfoxides will be main product of the polysulfide oxidation.…”
Section: Preparative Strategies For Polysulfidesmentioning
confidence: 99%
“…When T 0 was set at T g −30 K, the data points consistently fitted better. Setting T 0 to be 30-50 K below the T g is a common practice during curve fitting of the VTF equation and has been reported previously for polyphosphazene solid polymer electrolytes [26]. If the T 0 value was set as T g in the VTF equation, it might be assumed that the segmental motion of the polymer is the rate limiting step in ionic conduction.…”
Section: Ionic Conductivity Behaviormentioning
confidence: 99%
“…However, PEOLiX complexes exhibit very low ambient conductivity, typically 10 −7 S/cm. Recently, several classes of polymer electrolytes based on comb polyphosphazene [17][18][19][20][21][22][23][24][25], polysiloxane [26][27][28][29][30][31][32][33][34][35] and borane containing polyethers [36] were found to exhibit higher ambient ionic conductivity. These results demonstrated that apWe dedicate this paper to Professor Dick Jones, polysilane pioneer and valued friend.…”
Section: Introductionmentioning
confidence: 99%